Conventional Synthetic Disease-Modifying Anti-rheumatic Drugs for Psoriatic Arthritis: Findings and Implications From a Patient Centered Longitudinal Study in Brazil - Faria, Ronaldo José; Cordeiro, Francisca Janiclecia Rezende; dos Santos, Jéssica Barreto Ribeiro; Alvares-Teodoro, Juliana; Guerra Júnior, Augusto Afonso; Acurcio, Francisco de Assis; da Silva, Michael Ruberson Ribeiro (Frontiers in Pharmacology, 2022)
Background: Conventional synthetic disease-modifying antirheumatic drugs are the first-line treatment to inhibit the progression of psoriatic arthritis. Despite their widespread clinical use, few studies have been conducted to compare these drugs for psoriatic arthritis. Methods: a longitudinal study was carried out based on a centered patient national database in Brazil. Market share of drugs, medication persistence, drug costs, and cost per response were evaluated. Results: a total of 1,999 individuals with psoriatic arthritis were included. Methotrexate was the most used drug (44.4%), followed by leflunomide (40.6%), ciclosporin (8.2%), and sulfasalazine (6.8%). Methotrexate and leflunomide had a greater market share than ciclosporin and sulfasalazine over years. Medication persistence was higher for leflunomide (58.9% and 28.2%), followed by methotrexate (51.6% and 25.4%) at six and 12 months, respectively. Leflunomide was deemed the most expensive drug, with an average annual cost of $317.25, followed by sulfasalazine ($106.47), ciclosporin ($97.64), and methotrexate ($40.23). Methotrexate was the drug being the lowest cost per response. Conclusion: Methotrexate had the best cost per response ratio, owing to its lower cost and a slightly lower proportion of persistent patients when compared to leflunomide. Leflunomide had a slightly higher medication persistence than methotrexate, but it was the most expensive drug.